Performance of a Sulfide-Oxidizing, Sulfur-Producing Membrane Biofilm Reactor Treating Sulfide-Containing Bioreactor Effluent - Sahinkaya, Erkan; Hasar, Halil; Kaksonen, Anna H.; Rittmann, Bruce E. (Amer Chemical Soc, 2011)
Sulfide-containing waste streams are generated in mining, petrochemical plants, tanneries, viscose rayon manufacture, and the gasification of coal. Colorless sulfur bacteria can oxidize sulfide to elemental sulfur (S degrees), which can be recovered, when oxygen is their electron acceptor. This study evaluated sulfide oxidation and S degrees recovery in an oxygen-based membrane biofilm reactor (MBfR) treating the effluent from a sulfidogenic anaerobic baffled reactor. Sulfide oxidation efficiency (37-99%) and S degrees recovery (64-89% of oxidized sulfide) could be controlled by manipulating the sulfide loading oxygen pressure to the fibers, and hydraulic retention time (HRT). For example, too-low oxygen pressure decreased S degrees recovery due to decreased sulfide oxidation, but too-high oxygen pressure lowered S degrees recovery due to its oxidation to sulfate. Most importantly, high sulfide oxidation (>98%) and conversion to S degrees (>75%) could be achieved together when the sulfide loading was less than 1.7 mol/m(2).d and the O(2) pressure was sufficient to give an O(2) flux of at least 1.5 mol/m(2).d. However, higher sulfide loading could be compensated by a higher O(2) pressure, and the best performance occurred when the sulfide loading was high (2 molS/m(2).d), the O(2) pressure was high (similar to 1 atm), and the HRT was short (1.9 h). Membrane fouling caused a low O(2) flux, which led to low sulfide-oxidation efficiency, but fouling could be reversed by mild acid washing.
Keywords: Containing Waste-Water; Anaerobic Baffled Reactor; Fluidized-Bed Reactor; Simultaneous Removal; Nitrogen-Compounds; Organic-Matter; Reduction; Biotreatment; Perchlorate; Oxidation